Financing imports, the Triffin dilemma and more - Alessandro Saccal (Economics and Econometrics Research Institute (EERI), 2023)
This paper presents a formal proof of the notion by which a country devoid of tradable assets and without access to foreign borrowing and lending must systematically pay for its imports in foreign currency through its exports alone, provided a demand for them to begin with. It likewise sets forth a formal proof of the Triffin dilemma, by which a country whose external currency enjoys the status of an international reserve currency is bound to incur a trade deficit and an attendant excess of extant foreign net borrowing in relation to its tradable assets, meanwhile advancing an innovative, orderly model of the balance of payments. Currency regimes, sudden stops in foreign net borrowing, international reserve currencies and changes in private and public consumption are additionally examined. This monograph completes its study of the dynamics pertaining to exports and foreign borrowing by means of a static deterministic partial equilibrium (SDPE) model, via stability analysis.
Keywords: E12; F13; F30; F31; F41; F45; F52; N10; 330; balance of payments; exports; imports; international reserve currency; Triffin dilemma; tradable assets